Efektivitas Ekstrak Kulit Buah Maja Sebagai Inhibitor pada Baja Karbon Aisi 1020 dalam Medium Korosif Nacl 3% dengan Variasi Waktu Perendaman - Ismi Nurhayati; Pulung Karo Karo; Syafriadi Syafriadi (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2020)
Research has been conducted on the effectiveness of maja fruit skin extract as an inhibitor of carbon steel AISI 1020 in a corrosive medium NaCl 3% with variations in immersion time. The samples carbon steel AISI 1020 were immersed in corrosive medium NaCl 3% without being given and given the inhibitor of maja skin extract with a concentration of 0.8% for 5, 15, 25, 35, and 45 days. Calculation of reduction in corrosion rate is carried out by the method of weight loss. The results showed that the addition of the maja fruit skin extract inhibitor was effective in reducing the corrosion rate of the sample with the greatest efficiency at 35 days immersion, which was equal to 72.35%. The results of XRD characterization show that the phase formed is pure Fe and Fe3O4 phase which is a corrosion product is immersed without inhibitor. The results of SEM characterization showed that the microstructure of the surface of the sample after immersion was there were cracks, holes, and lumps which indicated that the sample had been corroded. The results of EDS characterization show that in the soaked sample there were corrosion products in the form of FeO compounds whose magnitude increased every time immersion.